Professional practice models used by nurses in Portuguese hospitals - Olga Maria Pimenta Lopes Ribeiro; Maria Manuela Ferreira Pereira da Silva Martins; Daisy Maria Rizatto Tronchin; João Miguel Almeida Ventura da Silva; Elaine Cristina Novatzki Forte
ABSTRACT Objective: To analyze the professional practice models used by nurses in the hospital context. Method: A descriptive study with a qualitative approach was carried out in 19 hospitals with 56 nurses. Data collection was carried out by means of a semi-structured interview. Results: The following categories emerged from analysis: a practice focused on the management of signs and symptoms, where the biomedical model, prevention of complications, and early detection of signs and symptoms of clinical worsening stood out, and a practice based on patients' human responses, emphasizing health promotion, self-care promotion, autonomy reconstruction, functional rehabilitation, patients' training, preparation to return home, and facilitation of transitions. Final considerations: In spite of the evolution seen in some contexts, a distance between the models practiced and those presented is still found, which indicates the need for changes ensuring structuring and systematization of the professional practice.